Etude de la station d’épuration de la ville d’Ain Fakroun a base de boue activée - Zakaria Chenta (My University, 2026)
This study aims to design a wastewater treatment plant for the municipality of Aïn Fakroun in order to reduce river pollution and contribute to environmental protection. The adopted methodology is based on a detailed analysis of wastewater characteristics, together with the study of the biological treatment process using activated sludge, as well as the evaluation of disinfection efficiency using sodium hypochlorite (bleach). The results showed a significant improvement in treated water quality, thereby enhancing environmental protection and reducing pollution impacts. ------------------------------------------------------------------------- يهدف هذا البحث إلى تصميم محطة لمعالجة مياه الصرف الصحي ببلدية عين فكرون، قصد الحد من تلوث الوادي والمساهمة في حماية البيئة. وتعتمد الدراسة على تحليل دقيق لخصائص المياه المستعملة، مع دراسة عملية المعالجة البيولوجية بالحمأة المنشطة، بالإضافة إلى تقييم فعالية التطهير بمادة الجافيل. وقد أظهرت النتائج تحسنًا واضحًا في جودة المياه المعالجة، مما ساهم في تعزيز حماية البيئة والحد من آثار التلوث. ---------------------------------------------------------------------- Cette étude vise à concevoir une station d’épuration des eaux usées pour la commune d’Aïn Fakroun afin de réduire la pollution de l’oued et de contribuer à la protection de l’environnement. La méthodologie adoptée repose sur une analyse détaillée des caractéristiques des eaux usées, ainsi que sur l’étude du procédé de traitement biologique par boues activées, en plus de l’évaluation de l’efficacité de la désinfection à l’eau de Javel. Les résultats obtenus montrent une amélioration significative de la qualité des eaux traitées, contribuant ainsi au renforcement de la protection de l’environnement.
Keywords: Wastewater treatment plant; river pollution; activated sludge; disinfection using sodium hypochlorite (bleach).; محطة معالجة مياه الصرف الصحي، تلوث الوادي، الحمأة المنشطة، التطهير بمادة الجافيل; Station d’épuration des eaux usées; pollution de l’oued; boues activées; désinfection à l’eau de Javel